Fatigue crack growth behavior of Inconel 718 produced by selective laser melting (Fracture and Structural Integrity, 2015)
Additive layer manufacturing has recently gained a lot of interest due to the feasibility of producing metallic components directly from a computer-aided design file of the part. Selective laser melting, one of the main additive layer manufacturing technologies, is currently capable of producing nearly ready-to-use parts made of metallic materials. Their microstructure, however, differs substantially from that produced by conventional manufacturing. That is why a detailed study and knowledge of the relation of specific microstructure, parameters of the selective laser melting process and mechanical properties is of utmost significance. This study reports on the investigation of the fatigue crack growth behavior in Inconel 718 superalloy produced by selective laser melting. The fatigue crack growth curve and the threshold values of the stress intensity factor for propagation of long cracks were experimentally determined on compact-tension specimens fabricated using a RENISHAW A250 system and the recommended processing parameters. The fatigue crack growth rates and the fatigue crack paths both in the threshold and in the Paris region were investigated. The crack propagation curves and the crack propagation threshold were compared with literature data describing the behavior of conventionally manufactured material. The mechanism of fatigue crack growth was discussed in terms of the specific microstructure produced by selective laser melting.
Keywords: Inconel 718; selective laser melting; Fatigue crack growth; Fractography